Accuracy of Fingerprint Pulse Oximeter Compared to Neonatal Pulse Oximetry in Early Detection of Critical Congenital Heart Disease in Newborn Infants - Linda Silvana Sari; Titi Pambudi Karuniawaty; Putu Aditya Wiguna; Wayan Sulaksamana Sandhi Parwata (Jurnal Penelitian Pendidikan IPA, 2025)
Critical congenital heart disease (CHD) requires immediate diagnosis and intervention, but its asymptomatic nature in early life presents a significant challenge for detection. This study aimed to determine the suitability of a common fingertip pulse oximeter as a low-cost screening tool compared to the standard neonatal pulse oximeter for the early detection of critical CHD. A cross-sectional study was conducted with 150 newborn subjects at a health center in Kediri. The results indicated that while the neonatal pulse oximeter measured pulse frequency and saturation more quickly, there was no statistically significant difference in the preductal (p=0.053) and postductal (p=0.099) oxygen saturation values recorded by the two devices. However, despite a weak positive correlation, a Bland-Altman analysis revealed poor agreement and reliability between the two instruments, with an average bias of 0.93% (95% CI: -7.38 to 9.24) for preductal and 0.74% (95% CI: -8.49 to 9.24) for postductal measurements. In conclusion, although no subjects were diagnosed with critical CHD, the findings suggest that the fingertip pulse oximeter is not a sufficiently reliable substitute for neonatal pulse oximetry in screening for this condition due to the poor agreement between the two methods.